The role of english communication skills in increasing students' competitiveness - Harahap, Sriwida; Lumbantobing, Kesya Nirma; Panjaitan, Berkat (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
The ability to speak English has a significant impact on job advancement, expanding business networks, and allowing all parties to pursue career opportunities in response to economic changes. In recent decades, Asia has emerged as a driving force in global economic growth, led by leaders who established international relationships and founded multinational corporations. Economic competition in the private sector has prompted many businesses to actively prioritize English language skills and invest in English language development. This condition necessitates the use of suitable methods of learning in a foreign tongue. The purpose of the current research is to assess students' proficiency in communicating in English using the Semantic Mapping strategy. The results of this study show that the English communication skills of the Electromedical Technology study program are in.